Pilot-scale anaerobic co-digestion of food and garden waste: Methane potential, performance and microbial analysis. (February 2022) - Borth, Priscila Liane Biesdorf; Perin, Jessica Klarosk Helenas; Torrecilhas, Arthur Ribeiro; Lopes, Daiane Dias; Santos, Samantha Christine; Kuroda, Emília Kiyomi; Fernandes, Fernando
Abstract: Among the organic waste sources used for energy recovery through anaerobic digestion, food waste can be emphasized, as they are the result of the growing demand for food in the world. Additionally, lignocellulosic waste is one of the major energy sources available in urban and rural areas. In this context, the objective of this research was to evaluate the effects of food and garden waste co-digestion in the anaerobic process performance and also in the microbial community involved, by comparing two pilot scale reactors (500 L). To enable the comparison between mono-digestion and co-digestion, one reactor was operated only with food waste as a substrate while in the other, 20% of the ORL from the food waste was substituted by garden waste. The results showed a better performance in co-digestion, with a removal of 83% in VS, an average specific methane yield of 0.47 LCH4 gVS −1, a biogas production rate of 86 L d −1, with an average methane content of 67% and a delay in the system acidification when an OLR of 0.24 kgVS m −3 d −1 was applied. The SEM images showed that the microorganisms were attached to garden waste particles as support medium for biofilm formation, favoring the development of certain species of microorganisms more resistant to external variations and, consequently, delaying the acidification of the reactor. The analysis of the microbial community in the reactors indicated a higher presence of hydrogenotrophic methanogenic archaea ( Methanospirillum, Methanobacterium, Methanobrevibacter and Methanoculleus ). Graphical abstract: Image 1 Highlights: Co-digestion improved methane production and delayed the system acidification. The microbial community used garden waste as support for biofilm formation. There was variation in the diversity and abundance of bacteria and archaea. A greater presence of hydrogenotrophic methanogens was identified in both reactors.